Utilization of cow dung as a biogas raw material for alternative energy in Buddagan 1 Hamlet, Kabupaten Pamekasan - Anggono, Willyanto; Hernando, Ivan Christian; Tulistyantoro, Lintu (Universitas Muhammadiyah Magelang, 2025)
Buddagan 1 Hamlet, Pamekasan Regency, faces the problem of cow dung waste piling up around the house, causing an unpleasant odor and unhygienic kitchen conditions. The proximity of the cow shed to the kitchen, coupled with the status of a heritage village that requires a solution without changing the building structure, demands an innovative approach. Therefore, this community service aims to apply biogas technology to utilize cow dung waste as an alternative energy source, improve environmental cleanliness, and reduce household expenses. Community service activities include socialization of biogas technology, training on use and maintenance, as well as installation and evaluation assistance. As a result, biogas technology was successfully implemented, meeting cooking gas needs, reducing household costs, and producing organic fertilizer. Socialization, training, and ongoing assistance ensure the operational success of biogas technology. Buddagan 1 Hamlet is now an inspiring example of environmentally friendly livestock waste management.